YouTuber Village: Digital Literacy Transformation and Economic Independence for the Tapen Village Community in Bondowoso - Abdul Jalel; Ahmad Abqoriyin Hisan (The Eastasouth Journal of Social Science and Humanities, 2026)
Advances in information and communication technology have opened up opportunities for economic digitalization in rural areas. One notable phenomenon is the economic transformation in Tapen Village, Tapen District, Bondowoso Regency, widely known as the "YouTuber Village." Many local youths have transitioned to digital content creation to earn independent income directly from their village. This study aims to analyze the use of the YouTube platform as an instrument to increase community work productivity, identify content monetization strategies implemented by the community, and examine its financial impact on the economic independence of rural youth. This research employed a qualitative approach with a case study method. Data were collected through participant observation, documentation, and in-depth interviews with movement pioneers, aspiring content creators, and community leaders in Tapen Village. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Field findings indicate that the use of YouTube has successfully transformed the productivity landscape of communities through a work-from-home system. The success of Google AdSense monetization is driven by a knowledge transfer system through peer tutoring among residents. This phenomenon has significantly impacted reducing the urbanization rate of young school graduates, improving family financial well-being, and optimizing the new media-based creative economy in rural areas.